BRAINIAC: The Planning Process for the E-Learning Platform with Text Summarisation Tools - Siti Nur Fatehah Nordin; Nurdiana Azizan; Noraizah Abu Bakar; Dini Onasis (Malaysian Journal of Science Health & Technology, 2025)
This paper presents the planning process for the BRAINIAC, an e-learning platform with text summarisation tools. The evolution of technology in education happens gradually throughout daily lives, from the old traditional method to the digital process, making the educational experience easier and more convenient. E-learning, which uses electronic devices and digital resources, has become essential, especially during the COVID-19 pandemic. Despite the widespread use of e-learning platforms such as Moodle, Google Classroom, Blackboard, and Udemy, it still lacks an integrated text summarisation tool. This tool is vital for helping learners efficiently process and comprehend extensive textual information. This project, Brainiac, aims to develop an e-learning platform, which is a web-based application that incorporates Artificial Intelligence (AI) and Natural Language Processing (NLP) for text summarization. The methodology used to ensure the development process runs smoothly for this project is the Agile Model. The research objectives are to identify gaps in existing e-learning platforms, propose a robust security framework for Brainiac, and evaluate its accuracy and compatibility through thorough testing. Hence, Brainiac aims to enhance learning, improve comprehension, and save time for users, thus significantly enhancing the overall effectiveness of digital education. The implication of Brainiac could revolutionise digital education by improving information processing and comprehension, ultimately enhancing learning efficiency and user experience. In conclusion, Brainiac’s text summarisation tools significantly advance e-learning, offering a transformative approach to improving information processing, comprehension, and overall educational efficiency.